Supply chain resilience and key performance indicators: a systematic literature review - Karl,Alexandre Augusto (2018)
Abstract Paper aims The aim of this article is to explore the influence of non-financial key performance indicators (KPIs) to create supply chain resilience (SCRes). Originality It theoretically identifies the influence of specific non-financial KPIs when creating SCRes by monitoring them before, during and after a disruption. Research method A systematic literature review was conducted using 57 peer-reviewed academic papers from 2000 to 2017. Main findings Order and delivery lead time, on-time delivery, supplier delivery efficiency and customer satisfaction were the KPIs that had a significant influence on elements of resilience. Implications for theory and practice Results contribute to the theory by providing knowledge in an underexplored topic, and assist managers in practice by identifying specific KPIs to build resilience.